Changes of bone mineral density and serum pentosidine during a 27-month follow-up of monthly minodronate in osteoporotic patients. (3rd July 2017) - Ohishi, Tsuyoshi; Fujita, Tomotada; Suzuki, Daisuke; Nishida, Tatsuya; Yamamoto, Kazufumi; Okabayashi, Ryo; Ushirozako, Hiroki; Banno, Tomohiro; Matsuyama, Yukihiro
ABSTRACT: Purpose : Monthly regimen of minodronate for osteoporosis more than two years has not been reported yet. The aim of this study is to elucidate the effect of monthly minodronate (M-MIN) on bone mineral density (BMD) and serum pentosidine (Pen) during 27 months.Materials and methods : The study consisted of 52 newly treated patients (73.3 ± 8.8 years) (new group) and 47 patients (75.9 ± 9.5 years) who were switched from either alendronate or risedronate (switch group). Monthly minodronate (50 mg/every 4 weeks) was administered for 27 months. Lumbar, femoral neck, and total hip BMDs and serum pentosidine were monitored at baseline and after 9, 18, and 27 months of treatment.Results : In the new condition, lumbar, neck, and total hip BMDs increased significantly by 9.07%, 3.15%, and 3.06%, respectively. Only the lumbar BMD significantly increased in the switch condition. Serum Pen increased in both groups in a time-dependent manner. In the group switch, multivariate logistic regression analysis revealed that the initial change in serum intact procollagen type I N-terminal propeptide (P1NP) at 9 months was an independent predictor of changes in neck and total hip BMDs at 27 months (OR = 1.039, 95% CI 1.003–1.077, p = 0.032 for neck and OR = 1.055, 95% CI 1.009–1.104, p = 0.020 for total hip).Conclusions : Monthly minodronate treatment increased BMDs in newly treated patients over 27 months. Serum Pen increased with M-MIN therapy, possibly indicating prolonged bone turnover. The initial 9-month changes in serum P1NP predicted the 27-month changes in hip BMDs when M-MIN replaced alendronate or risedronate.